Phenylisoxazole-3/5-Carbaldehyde Isonicotinylhydrazone Derivatives: Synthesis, Characterization, and Antitubercular Activity. (31st October 2021) - Carrasco, Fernando; Hernández, Wilfredo; Chupayo, Oscar; Sheen, Patricia; Zimic, Mirko; Coronel, Jorge; Álvarez, Celedonio M.; Ferrero, Sergio; Oramas-Royo, Sandra; Spodine, Evgenia; Rodilla, Jesus M.; Dávalos, Juan Z.
Abstract : Eight new phenylisoxazole isoniazid derivatives, 3-(2′-fluorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (1 ), 3-(2′-methoxyphenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (2 ), 3-(2′-chlorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (3 ), 3-(3′-clorophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (4 ), 3-(4′-bromophenyl)isoxazole-5-carbaldehyde isonicotinylhydrazone (5 ), 5-(4′-methoxiphenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (6 ), 5-(4′-methylphenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (7 ), and 5-(4′-clorophenyl)isoxazole-3-carbaldehyde isonicotinylhydrazone (8 ), have been synthesized and characterized by FT-IR, 1 H-NMR, 13 C-NMR, and mass spectral data. The 2D NMR ( 1 H- 1 H NOESY) analysis of 1 and 2 confirmed that these compounds in acetone-d6 are in the trans(E) isomeric form. This evidence is supported by computational calculations which were performed for compounds 1 –8, using DFT/B3LYP level with the 6-311++G(d, p) basis set. The in vitro antituberculous activity of all the synthesized compounds was determined against the Mycobacterium tuberculosis standard strains: sensitive H37Rv (ATCC-27294) and resistant TB DM97. All the compounds exhibited moderate bioactivity (MIC = 0.34–0.41  μ M) with respect to the isoniazid drug (MIC = 0.91  μ M) against the H37Rv sensitive strain. Compounds 6 (X = 4′-OCH3 ) and 7 (X = 4′-CH3 ) with MIC values of 12.41 and 13.06  μ M, respectively, were about two times more cytotoxic, compared with isoniazid, against the resistant strain TB DM97.